Pregoreksja – jadłowstręt psychiczny kobiet w ciąży - Cichecka-Wilk, Małgorzata (Studia Edukacyjne, 2021)
Pregorexia is the term used to describe anorexia nervosa in pregnant women. It is not a medical term, yet increasingly used by specialists nowadays. Probably this is because the cases of pregorexia they encounter in practice are increasing in number, affecting 1.5–5% of women. In addition, they emphasize the specificity of this eating disorder, which carries a double risk when the mother is expecting. However, the latest classification of mental disorders of the American Psychiatric Association, DSM-5, does not include a separate name and criteria for the diagnosis of anorexia nervosa occurring in pregnant women. The clinical picture of pregorexia, apart from some significant symptoms, is consistent with the picture of this disorder in other people. Women with this disorder show a strong fear of the natural consequence of pregnancy, which is weight gain. To this end, they reduce the amount of food consumed, reduce the caloric content of meals, and use fasts. They also often do intense exercise. Sometimes they have binge eating and purging episodes, provoke vomiting, and abuse laxatives. As a result, they lose weight, develop qualitative malnutrition and body exhaustion. This entails numerous negative effects on the health and sometimes life of both mother and child. Such a danger, however, is not a factor preventing the actions causing it. They are caused by the pathological mechanism of the disorder, related to the action of various factors. In this article, some selected ones seem to be peculiarly significant in relation to pregorexia.